2019
DOI: 10.13031/aea.13203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drip Irrigation Regimes Under Plastic Film on Sugar Beet Yield and Water Use Efficiency in Xinjiang

Abstract: Abstract. This 2-yr study analyzed the effects of different irrigation regimes of drip irrigation under plastic film on sugar beet production in Xinjiang, China, and established a binary quadratic regression equation and normalization to describe the maximum root yield, sugar yield, and water use efficiency. Three irrigation frequencies (10, 11, and 12 d) and two irrigation water quotas (45 and 60 mm) were combined to form six treatments. Irrigation frequency had a significant effect on root yield at 1% level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Appropriately increasing the frequency of irrigation can effectively reduce the risk of cotton yield reduction. Studies by some scholars have shown that an increase in the frequency of irrigation can increase crop yield [ 29 , 30 ]. High-frequency irrigation concentrates water in a small area of the root zone, which promotes the growth of the cotton root system and the uptake and utilization of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately increasing the frequency of irrigation can effectively reduce the risk of cotton yield reduction. Studies by some scholars have shown that an increase in the frequency of irrigation can increase crop yield [ 29 , 30 ]. High-frequency irrigation concentrates water in a small area of the root zone, which promotes the growth of the cotton root system and the uptake and utilization of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have studied the effect of drip irrigation under different membranes on sugar beet production in Xinjiang. When the irrigation amount was 60 mm and the frequency was 11 d, the sugar yields of sugar beet increased by 10.8% and 6.5%, respectively [18].…”
Section: Introductionmentioning
confidence: 98%
“…This technology has the advantages of saving water and fertilizer [7], maintaining moisture and increasing temperature [8], and effectively increasing the growth of crop roots [9], thereby increasing cotton yield [10]. The area used for drip irrigation under film mulch has increased from 1.67 hm 2 in 1996 to the current 300 × 10 4 hm 2 [11]; and crops grown have extended to corn [12], sugar beet [13], wheat [14], potato [15], and maize [16] as food and cash crops. Some scholars have explored the sustainability of drip irrigation under film mulch [17,18].…”
Section: Introductionmentioning
confidence: 99%